AJTE 2017
DOI: 10.14221/ajte.2017v42n11.10
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers’ TPACK Development and Conceptions through a TPACK-Based Course

Abstract: This study examines pre-service teachers ' Technological Pedagogical Content Knowledge (TPACK)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 23 publications
4
38
0
1
Order By: Relevance
“…As regards the findings about the different domains of TPACK, the preservice teachers reported a significant increase in three main technology-related components including TCK, TPK and TPACK at post-survey. The finding is in line with previous numerous research (Durdu & Dag, 2017;Thomas & Edson & Abebe, 2018;Adams & Rojas, 2018;Lu et al, 2011) in which an intervention was implemented throughout a course led to TPACK growth. This is also supported and overlaps with the participants' achievement in lesson plans in which these TPACK components were also found to be good.…”
Section: Research Question 1: What Impact Did the Integration Of A Desupporting
confidence: 90%
“…As regards the findings about the different domains of TPACK, the preservice teachers reported a significant increase in three main technology-related components including TCK, TPK and TPACK at post-survey. The finding is in line with previous numerous research (Durdu & Dag, 2017;Thomas & Edson & Abebe, 2018;Adams & Rojas, 2018;Lu et al, 2011) in which an intervention was implemented throughout a course led to TPACK growth. This is also supported and overlaps with the participants' achievement in lesson plans in which these TPACK components were also found to be good.…”
Section: Research Question 1: What Impact Did the Integration Of A Desupporting
confidence: 90%
“…It would not be wrong to talk about technology integration in education for inexperienced teacher candidates (Kovalik, Kuo, & Karpinski, 2013). Therefore, gaining technology integration self-efficacy beliefs together with the transfer of TPCK competencies to a real class environment would overcome the problem by providing intensive microteaching experiences in the teacher education (Akkoc, 2011;Canbazoğlu-Bilici & Yamak, 2014;Cavin, 2008;Durdu & Dag, 2017;Hoffer & Grandgenett, 2012;Lee & Lee, 2014;Parsons & Stephanson, 2005;Sun, Strobel & Newby, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, researchers have focused on TPACK development of PSTs. The researchers have aimed to increase TPACK levels in PSTs using various methods, such as preparing and presenting TPACK-based lesson plans (Akyuz 2018;Agyei and Keengwe 2014;Chai and Koh 2017;Chai et al 2010;Dalal et al 2017;Koh et al 2017;Tokmak 2013;Tseng et al 2019), training and preparing lesson plans (Brinkley-Etzkorn 2018;Özgün-Koca et al 2011;Koh and Divaharan 2011;Niess 2005), training and preparing lesson plans, and presenting them using micro-teaching methods (Durdu and Dağ 2017). On the other hand, Jang (2010) and Jang and Chen (2010) suggested that peer coaching will lead to TPACK development in cooperative studies.…”
Section: Literature Review About Tpack Development Strategiesmentioning
confidence: 99%